Measurement of jet fragmentation in Pb+Pb and $pp$ collisions at $\sqrt{s_{NN}} = 5.02$ TeV with the ATLAS detector - ATLAS collaboration (2914 authors) (2019)
Submitted by Helmut Wolters (helmut@coimbra.lip.pt) on 2019-02-05T16:23:21Z No. of bitstreams: 2 1.pdf: 1804467 bytes, checksum: 9d3b86a17c9b829e38da88e6e95c6e9f (MD5) zip/1673177.zip: 1211017 bytes, checksum: 82d3a0e7157d825aebebbcb86953e036 (MD5)